The duty of states to activate legislative harmonization in line with international humanitarian law conventions - إبراهيم, محمد (Latakia University Journal - Economic and Legal Sciences Series, 2022)
To take international humanitarian law agreements, legislative measures must be taken by the concerned countries to chase and prosecute people who are accused of committing violations of the provisions of international humanitarian law, and this requires states' commitment to legislative harmonization between their legislation and international humanitarian law agreements. This research dealt with the study of the theoretical trends to activate the legislative harmonization by showing its legal basis and theoretical methods. Then it dealt with harmonization from its practical side by studying the ways of legislative harmonization in European countries and then Arab countries.